Building Bridges: The Effective Learning Adviser as Transcultural and Cross-Disciplinary Communicator - Bohlmann, Julia (Journal of Academic Writing, 2020)
Out of 31,060 students currently enrolled at the University of Glasgow, about 25% are classed as international, reflecting a nationwide trend. In response to this situation, researchers and practitioners have stressed the need to improve the way universities accommodate multicultural student bodies. At the University of Glasgow, such efforts manifest in an expansion and diversification of the department facilitating student learning development: The Learning Enhancement and Academic Development Service (LEADS). LEADS is home to two Effective Learning Advisers (ELAs) who work with international students from all subject disciplines. Their work entails the creation and delivery of academic writing classes, the development of electronic resources and one-to-one tutorials. Due to the diversity of the international student cohort in terms of educational, cultural and subject backgrounds, a significant proportion of the international ELAs’ day-to-day job is to explain generic academic writing conventions pertinent to the UK Higher Education context to those coming from other educational cultures. Their role then is that of multicultural and cross-disciplinary communicators. This article outlines and reflects on the professional practice of the international ELAs and seeks to stimulate discussion around appropriate and effective practices of teaching academic writing to students from a multiplicity of backgrounds and disciplines.